THE IMPACT OF DIGITAL NARRATIVES ON LANGUAGE EVOLUTION:A COMPARATIVE STUDY OF ONLINE LITERATURE AND LINGUISTIC SHIFTS IN INTERNET SLANG (Contemporary Journal of Social Science Review, 2025)
In this paper, the researcher investigates how digital storytelling and internet slang are influencing the evolution of language, especially the merging of online literature and social media. By using a comparative analysis of Wattpad, AO3, Medium posts, Tik Tok, Reddit, and X posts across 2023 and 2025, the study quantifies how often, how widespread, and pragmatically useful slang is. The quantitative data show that there was constant increase in the use of slang in literature and in social media with online literature using about 59 % of slang tokens and the social media using 41% ones. Qualitative inquiry proves that the slang serves as a symbol of identity, cultural belonging, humour, and authenticity in narrative and also show morphological adaptation and semantic shift. The results show that digital slang does not imply the linguistic decadence, instead, it triggers creativity and cultural output, and, therefore, the bi-directional co-evolution of language and digital culture. Therefore, the given research will contribute to both sociolinguistics and literary studies by showing how informal digital registers become ingrained in the framework of structured narrative forms.